Natural Language Processing with Python Quick Start Guide Going from a Python Developer to an Effective Natural Language Processing Engineer. - Kasliwal, Nirant (Packt Publishing Ltd, 2018)
NLP in Python is among the most sought-after skills among data scientists. With code and relevant case studies, this book will show how you can use industry grade tools to implement NLP programs capable of learning from relevant data. We will explore many modern methods ranging from spaCy to word vectors that have reinvented NLP.